EVALUATION OF THE EFFECTS OF A PHYSICAL EXERCISE PROGRAM IN THE SATISFACTION WITH WORK AND IN THE PERCEIVED PRODUCTIVITY OF PUBLIC EMPLOYEES (Fiep Bulletin - online, 2015)
Few studies have used indirect calorimetry during swimming to estimate the energy cost of competitive swimmers and their association with cinematic parameters. Therefore, the aims of the present study were: i) to describe the aerobic and anaerobic energy production during the 200m breaststroke event; ii) to investigate the association between those variables and cinematic parameters during the event; iii) to investigate the association between physiological and mechanical parameters with the performance over the same distance. The sample included 12 breaststroke swimmers of national competitive level, with a mean (±SD) age of 17,42 ± 2,37 years, a mean weight (±SD)of 67,07 ± 6,26 kg, a mean height (±SD) of 1,74 ± 3,28 metros, a mean (±SD) arm span of 182,64±4,49 metros, a mean (±SD) body fat of 8,12±2,81 % and with a mean (±SD) of 10,71±2,21 years of training. The swimmers were submitted to a progressive intensity exhaustive test and a maximal 200m breaststroke test, both on a 25m swimming pool and with a 24h time lag. During tests, oxygen uptake and post exercise blood lactate were assessed. The tests were video recorded and the images were digitalized to calculate the vertical oscillation of the centre of mass (OV) and the intra cycle horizontal velocity variation (VIV). The anaerobic and aerobic fractions of total energy released during the 200m event were 18% and 82%, respectively. No association was found between these variables and the performance. The energy cost of swimming correlated negatively with OV and positively with VIV. None of the cinematic variables have correlated with the performance over the 200m distance.
Keywords: energy cost; breaststroke; performance; cinematic parameters